O gótico e as sombras: comunicação não comunicada - Dimarch, Bruno Fischer (2007)
The present Dissertation devotes to think about the Gothic, identifying the problems brought by the mistaken media exposition. For this purpose, it is presented a gothic reading of the Goth, so that it can be understood as a part of an usual process to all cultures, as a refuge of the generation of the, named here, culture norm . This research present as the theoretical corpus the General Systems Theory, in the development of Jorge de Albuquerque Vieira, proposing a new approach of the concept of collective shadow proposed by Carl Gustav Jung (1875-1961), from the hypothesis that every culture projects its shadow (the term culture refers only to western culture in this dissertation). This shadow is the allegoric night of moral, ethics and dominant customs. The repressed elements are organized in a system of mediation in the communicative relation of body with environment, named Shadows . Goth is a subsystem of Shadows, which found a great difficult in media communication. Through broadcasted interviews, sites and journalistic subjects in several means of communication, it is possible to find Goth associations with a culture and life style that are subversive, licentious, antichrist, necrophile etc. That kind of mediatic exposition, injured public identification in relation to Gothic culture. Although, the Goth intracommunication ensured its permanence and evolution, retreated from mediatic light. In the Shadows, this process points towards a relative distinction of the other subsystems and a specialization of its internal information. Besides the bibliographic research, interviews and an image documentary research in different media means were held